Hubungan Persepsi Visual Gambar Bahaya Merokok pada Bungkus Rokok dengan Perilaku Merokok Remaja Laki-laki di SMK X Banjarbaru - Nurlikasari, Anggelia; Rachmawati, Kurnia; Rahmayanti, Devi (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2021)
Smoking is a behavior that can make the appearance of various kinds of health disorders because cigarettescontain harmful ingredients. Smoking habits carried out by adolescents should be preventable and the need forsupporting factors that can direct adolescents not to smoke. One of them is by the government's efforts byincluding a picture of a health warning on a cigarette wrapper. This government's efforts aim to provideinformation about the impact of smoking. Smoking habits carried out by teenagers are quite high and this canbe due to the views and perceptions believed about cigarettes. Perception can affect a person so that it canreflect behavior. The purpose of the study was to analyze the relationship of visual perception of images of thedangers of smoking on cigarette packs with the smoking behavior of adolescent boys at SMK X Banjarbaru.Non-experimental methods with correlational analytic design with cross sectional approach and probabilitysampling technique with proportionate stratified random sampling type were used in this study. This studyamounted 125 students as samples and samples will fill out the questionnaires that have been provided. TheChi-square test is used to analyze data. The results of the study (p-value= 0.005 < =0.05) which means thereis a visual perception of the dangers of smoking in cigarette packs with the smoking behavior of teenage boys inSMK X Banjarbaru. Smoking behavior in adolescents can be prevented and controlled with a positiveperception of the image contained in cigarette packs